Differences in the prognostic value of tumor size on hepatocellular cancer-specific survival stratified by gender in a SEER population-based study. Issue 7 (August 2019) - Zhang, Wenjie; Jin, Kangpeng; Wang, Fei; Zhangyuan, Guangyan; Yu, Weiwei; Liu, Yang; Zhang, Haitian; Zhang, Ping; Sun, Beicheng
Background and objective: Tumor size is an important prognostic factor in cancers. This study aims at investigating the interaction between gender status and tumor size to evaluate cancer-specific survival (CSS) in hepatocellular carcinoma (HCC). Methods: In this study, we searched Surveillance, Epidemiology, and End Results (SEER) population-based data and identified 38, 368 patients diagnosed with HCC between 1988 and 2012. Patients diagnosed between 1998 and 2007 were distributed into a training set ( n  = 19279), and the rest were assigned as a SEER validation set ( n  = 19089). Definition of cut-off value of tumor size stratified by gender was determined by the "X-Tile" program. The five-year CSS data were found. Long-term survival outcomes and risk factors were analyzed by the Kaplan–Meier methods and the multivariable Cox regression models. Results: There were significant differences among these different tumor size subgroups with regards to five-year CSS ( p  < 0.001). When applying cutoff points of 38 mm and 75 mm tumor size in men, and 38 mm and 55 mm in women, the most significant difference was observed by the X-Tile program, respectively ( p  < 0.001). The five-year CSS was 27.5% for women and 25.7% for men in the training set, and 33.9% for women and 31.1% for men in the validating set ( p  < 0.001). Further analysis showed that this significant difference existed in localized, regional, and distant-stage patients. Conclusions: These results demonstrated that women with HCC appeared to exhibit better survival rates than men. The sex-related discrepancies should be emphasized, particularly for HCC patients with 39 to 75 mm tumors.